Rancang Bangun Smart Pond Berbasis Internet Of Things (IoT) - Muhammad Faris Rian Yazid; Diana Alia; Faris Nofandi (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
In the hold of the fishing boat, it is currently unable to control the pH of the water in accordance with the living environment of the fish. The pH of the water also needs to be considered so that the fish can survive. In addition, fish feeding on fishing vessels is also very necessary. The purpose of this research is to design a system that can control pH, fish feeding, fish water replacement. in the fish hold using an IoT-based microcontroller. The method used in this research uses quantitative methods through system design, design software design models, product trials.This method is used This research method includes steps taken to design and implement the system, as well as tests carried out to ensure the performance and success of the designed system. The results of the data designed by the system are analyzing the data in testing this tool according to its function. The accuracy of using the tool when feeding is 90.5% and the percentage error is 9.5%. The accuracy of using the tool when draining mode is 100% with a percentage error of 0%. And for the results of the percentage error of the pH sensor when the mode is on by 100% with a percentage error of 0%. This shows that the Smart Pond system designed has a high level of accuracy in terms of fish feeding and pond draining.